Comparing numerical ice-sheet model output with radio-echo sounding measurements in the Weddell Sea sector of West Antarctica. Issue 81 (28th April 2020) - Jeofry, Hafeez; Ross, Neil; Siegert, Martin J.
Abstract: Numerical ice-sheet models are commonly matched to surface ice velocities from InSAR measurements by modifying basal drag, allowing the flow and form of the ice sheet to be simulated. Geophysical measurements of the bed are rarely used to examine if this modification is realistic, however. Here, we examine radio-echo sounding (RES) data from the Weddell Sea sector of West Antarctica to investigate how the output from a well-established ice-sheet model compares with measurements of the basal environment. We know the Weddell Sea sector contains the Institute, Möller and Foundation ice streams, each with distinct basal characteristics: Institute Ice Stream lies partly over wet unconsolidated sediments, where basal drag is very low; Möller Ice Stream lies on relatively rough bed, where basal drag is likely larger; and Foundation Ice Stream is controlled by a deep subglacial trough with flow-aligned bedrock landforms and smooth unconsolidated sediments. In general, the ice-sheet model represents each ice-stream system well. We also find that ice velocities do not match perfectly in some locations, and that adjustment of the boundaries of low basal drag, to reflect RES evidence, should improve model performance. Our work showcases the usefulness of RES in calibrating ice-sheet model results with observations of the bed.